Themes highlighted in Malaysia and Singapore short stories from year 2000 to 2009: a review - Veeramohan Veeraputhran (Tanjong Malim, 2020)
Themes highlighted in Malaysia and Singapore short stories from year 2000 to 2009: a review by Veeramohan Veeraputhran